2023
DOI: 10.1021/jacs.3c03336
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Fluorescent Biosensors Based on Covalent DNA Anchors

Abstract: Semiconducting single-walled carbon nanotubes (SWCNTs) are versatile near-infrared (NIR) fluorophores. They are noncovalently modified to create sensors that change their fluorescence when interacting with biomolecules. However, noncovalent chemistry has several limitations and prevents a consistent way to molecular recognition and reliable signal transduction. Here, we introduce a widely applicable covalent approach to create molecular sensors without impairing the fluorescence in the NIR (>1000 nm). For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 67 publications
0
22
0
3
Order By: Relevance
“…Additionally, Weisman et al developed a protocol to covalently attach guanine bases to the lattice of SWCNTs. These defects cause quantum light emission from the coupled defect states. This approach can also be used directly for biosensing or conjugation of larger recognition motifs to create sensors for bacterial or viral motifs. , Diazonium chemistry also offers to conjugate more complex entities such as biomolecules. , It is useful to directly attach, for example, nanobodies or grow peptide chains on the SWCNT lattice, which expands the toolbox for many applications such as sensing with quantum defects. , The concentration of diazonium salt affects the reaction and, most likely, the density of quantum defects. The fluorescence intensity ratio I E 11 * / I E 11 between the quantum-defect-related emission (E 11 *) and the bandgap emission (E 11 ) of SWCNTs is regarded as an approximate measure for defect density .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Weisman et al developed a protocol to covalently attach guanine bases to the lattice of SWCNTs. These defects cause quantum light emission from the coupled defect states. This approach can also be used directly for biosensing or conjugation of larger recognition motifs to create sensors for bacterial or viral motifs. , Diazonium chemistry also offers to conjugate more complex entities such as biomolecules. , It is useful to directly attach, for example, nanobodies or grow peptide chains on the SWCNT lattice, which expands the toolbox for many applications such as sensing with quantum defects. , The concentration of diazonium salt affects the reaction and, most likely, the density of quantum defects. The fluorescence intensity ratio I E 11 * / I E 11 between the quantum-defect-related emission (E 11 *) and the bandgap emission (E 11 ) of SWCNTs is regarded as an approximate measure for defect density .…”
mentioning
confidence: 99%
“…This approach can also be used directly for biosensing or conjugation of larger recognition motifs to create sensors for bacterial or viral motifs. 38,39 Diazonium chemistry also offers to conjugate more complex entities such as biomolecules. 40,41 It is useful to directly attach, for example, nanobodies or grow peptide chains on the SWCNT lattice, which expands the toolbox for many applications such as sensing with quantum defects.…”
mentioning
confidence: 99%
“…As shown in Table S2, † the method had better performance in terms of both detection limit and linear range. [15][16][17][18][19][20] At the same time, the method used easily accessed materials and required no additional design of the aptamer segment, so it could be easily extended to the detection of other protein markers by simply changing the aptamer segment. Of course, the method also had some limitations.…”
Section: Papermentioning
confidence: 99%
“…Emerging aptamers with good binding affinity and speci-city provide opportunities for the establishment of detection methods for SARS-CoV-2 spike protein. [13][14][15][16][17][18][19][20] For example, Metternich et al made use of two aptamers targeting SARS-CoV-2 spike protein to develop a uorescence detection method based on covalent guanine quantum defect chemistry; 15 Luo et al demonstrated the usability of aptamer-functionalized MXene nanosheets as a novel sensor that allowed detection of SARS-CoV-2 spike protein down to 38.9 fg mL −1 ; 17 Xue et al reported an electrochemical method based on aptamer-binding induced multiple hairpin assembly and successfully applied it to detect as low as 9.79 fg mL −1 SARS-CoV-2 spike protein. 20 Although these methods have shown promising feasibility, they still have some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Dispersion of carbon nanotubes (CNTs), especially single-walled CNTs (SWCNTs), in water with the aid of surfactants is a well-established strategy used in many fundamental studies and technological applications. Ever since O’Connell et al first discovered that SWCNTs could be stabilized in water as individual nanotubes by the anionic surfactant sodium dodecyl sulfate (SDS) in 2002, many types of surfactants have been explored to form aqueous SWCNT solutions, including the anionic surfactant sodium dodecylbenzene­sulfonate (SDBS), the cationic surfactant cetyltrimethyl­ammonium bromide (CTAB), and the anionic bile salt surfactants sodium cholate (SC) and sodium deoxycholate (DOC). , Not surprisingly, the surfactant type and the surfactant assembly onto the nanotube can affect the surface potential of the surfactant–SWCNT complexes, resulting in different dispersion efficiencies . Many advanced studies of SWCNTs are thereby enabled, including nanotube sorting, ,, chemical reaction engineering, , fabrication of high-performance nanoelectronics devices, and the exploration of SWCNTs as biomedical drug/gene carriers and color center hosts. , …”
Section: Introductionmentioning
confidence: 99%